Resource Assessment of Tidal Stream Power in Pakiputan Strait, Davao Gulf, Philippines - Palconit, E. V.; Villanueva, J . R.; Enano, N. J.; Buhali, M. J.; Mascariñas, A. C.; Galope, G. E.; Tabanguil, J. M. (Engineering, Technology & Applied Science Research, 2021)
During the last years, there are ongoing efforts on the development of tidal energy conversion systems in the Philippines. This study conducts tidal energy resource assessment in the Pakiputan Strait following a methodology outlined as stage 2a tidal resource assessment published by the European Marine Energy Centre (EMEC). The study assessed the preliminary results of the tidal velocities at Pakiputan Strait with a mean spring peak velocity (Vmsp) of 1.7m/s at 3m from the water surface from 15 days of continuous data collection using a seabed-mounted acoustic Doppler current profiler. This corresponded to an estimated Annual Energy Production (AEP) of 1350kWh/y for 1m2 of capture area of the generic device. Sensitivity analysis showed that the spatial distribution of hydrodynamic model results does not vary significantly with variations in certain input parameters. It further showed that a 10% decrease in the nominal value of Vmsp on-site led to a 15% decrease in the nominal value of AEP, while a 10% increase in the nominal value of Vmsp led to a 30% increase in the nominal value of AEP, assuming that the considered Vmsp still corresponded to the velocity distribution from observations. A static survey and the use of computational fluid dynamics modeling are recommended to further enhance the analysis of the study.